How do single-family homeowners value residential and commercial density? It depends. (February 2022) - Acolin, Arthur; Colburn, Gregg; Walter, Rebecca J.
Abstract: This paper develops estimates of the relationship between local density and single-family home values using 2017 transactions for five U.S. metropolitan regions: Chicago, Los Angeles, Minneapolis, Philadelphia, Seattle. Proposals to build new commercial and residential development projects that would increase local density commonly face opposition from local homeowners. Academic literature links the response from homeowners to concerns that higher density is associated with lower property values but there is limited empirical evidence establishing this relationship at the local level. We find a positive and significant relationship between density and house value in the core area of the five metropolitan regions we analyze. Within 7.5 miles of the center of these metropolitan regions, a 10% increase in surrounding built area density is associated with a 1.1–1.9% increase in house prices per square foot. For outlying areas, the estimates are smaller and even negative in several cases. We instrument density based on topographic and soil characteristics and find similar results. These findings point to the need for a more nuanced discussion of the relationship between local density and housing values. Highlights: This paper estimates relationship between density and single family home values. Similar houses with higher density fetch higher prices in core areas. Relationship mixed in outlying areas. Depending on context homebuyers pay more for houses in higher density areas. Uses instruments for density: slopes and soil characteristics around property.